Discovery Model Strategy for learning Morphologie: Morphological Analysis of French-South Korean Cosmetic Brands - Syawalina, Lina; Umaya, Siti; Basarah, M. Farhan (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
Abstract The aim of this research is to enhance students' thinking abilities in Morphological Analysis in the Morphologie course through the implementation of the Discovery Learning teaching model, and to describe the learning process of the Morphologie course in the French Language Study Program at STBA YAPARI-ABA Bandung for the Academic Year 2019-2020. The data source for this research is South Korean cosmetic brands in the French language. The research method used is a qualitative method. The data collection techniques used are documentation, observation, using the listening method as the data collection method, and using tapping as the underlying technique. Data was collected from various sources, such as commercial advertisements in various media, cosmetic products sold in various shopping centres as well as online through e-commerce, and various Korean cosmetic websites. The data analysis technique used is the distribution method, with language itself as the determining element. The research findings indicate that there are only 2 morphological processes of South Korean cosmetic brands in the French language that adhere to the grammatical rules of the French language, and 26 morphological processes of South Korean cosmetic brands in the French language that do not comply with the grammatical rules of the French language. Top of Form Keywords:  discovery learning,; morphologie,;cosmetic brand;   Abstrak Tujuan utama dari penelitian ini adalah untuk meningkatkan kemampuan berpikir mahasiswa dalam Analisis Morfologis pada mata kuliah Morphologie melalui penerapan model pembelajaran Discovery Learning dan mendeskripsikan proses pembelajaran Mata Kuliah Morphologie di Program Studi Bahasa Prancis STBA YAPARI-ABA Bandung Tahun Akademik 2019-2020.Sumber data dalam penelitian ini adalah jenama Kosmetik Korea Selatan Berbahasa Prancis. Metode peneltian adalah metode kualitatif. Teknik pengumpulan data nyang digunakan adalah dokumentasi, observasi, menggunakan metode simak sebagai metode pengumpulan data dan menggunakan Teknik sadap  sebagai teknik dasarnya. Data disadap dari berbagai sumber, seperti iklan komersial di berbagai media, produk kosmetik yang dijual baik di berbagai pusat perbelanjaan maupun yang dijual secara daring dalam e-commerce, dan berbagai laman kosmetik Korea. Teknis analisis Data menggunakan metode agih yang unsur penentunya merupakan bahasa itu sendiri. Hasil penelitian menunjukan bahwa terdapat 2 proses morfologis jenama Kosmetik Korea Selatan berbahasa Prancis yang sesuai dengan kaidah gramatikal Bahasa Prancis, dan 26 proses morfologis jenama Kosmetik Korea Selatan berbahasa Prancis yang tidak sesuai dengan kaidah gramatikal Bahasa Prancis.   Kata Kunci: discovery learning,; morphologie,;jenama Kosmetik;